2020
DOI: 10.31616/asj.2020.0594
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in the Management of Osteoporotic Vertebral Fractures: A Narrative Review

Abstract: Vertebral fractures are the most common type of osteoporotic fracture and can increase morbidity and mortality. To date, the guidelines for managing osteoporotic vertebral fractures (OVFs) are limited in quantity and quality, and there is no gold standard treatment for these fractures. Conservative treatment is considered the primary treatment option for OVFs and includes pain relief through shortterm bed rest, analgesics, antiosteoporotic drugs, exercise, and braces. Studies on vertebral augmentation (VA) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 84 publications
1
22
1
1
Order By: Relevance
“…In the present case, a fracture developed at the thoracolumbar junction, which has been considered to be an unstable region because of the transition zone between long and stiff kyphotic thoracic spine and mobile lordotic lumbar spine. 10 Especially, IVC at 3 months after trauma suggested unstable fracture in this patient; this was different from previous reports and presented as collapsed anterior vertebral height in the standing position compared to the supine position ( Figure 4 ). 14 In case of definite fracture instability as present case, conservative treatment including teriparatide could be considered because patient complained of tolerable mechanical back pain without neurologic deficits.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present case, a fracture developed at the thoracolumbar junction, which has been considered to be an unstable region because of the transition zone between long and stiff kyphotic thoracic spine and mobile lordotic lumbar spine. 10 Especially, IVC at 3 months after trauma suggested unstable fracture in this patient; this was different from previous reports and presented as collapsed anterior vertebral height in the standing position compared to the supine position ( Figure 4 ). 14 In case of definite fracture instability as present case, conservative treatment including teriparatide could be considered because patient complained of tolerable mechanical back pain without neurologic deficits.…”
Section: Discussioncontrasting
confidence: 99%
“…1 , 3 Thus, surgical management is strongly recommended for stability of spinal column and fracture healing. 10 - 12 However, we report a first case of successful teriparatide treatment of unstable bony Chance fracture at thoracolumbar junction in DISH patient.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, it should be noted how calcium, vitamin D, and amino acids supplementation should be considered in a multidisciplinary integrated intervention combined with lifestyle education to prevent or to counteract the developing of osteosarcopenia [ 3 , 49 , 50 , 51 , 52 ]. Almost 70% of the PRM physicians involved prescribed therapeutic exercise in their clinical practice; these findings are in line with the available literature suggesting its beneficial effects of exercise in terms of pain, posture, physical performance, and HRQoL [ 53 , 54 , 55 , 56 , 57 ]. In this scenario, a recent Cochrane Systematic Review performed by Gibbs et al [ 58 ] supported exercise therapy as an effective intervention in functional outcomes improvement in patients suffering from osteoporotic vertebral fractures with moderate evidence.…”
Section: Discussionsupporting
confidence: 71%
“…However, studies have shown that approximately 30% of all OVCFs presents with progressive collapse, 13% accompanied with nonunion, and 3% develops delayed vertebral collapse (DVC) with neurologic deficits [ 1 , 2 ]. Moreover, osteoporosis may impair bone healing of the vertebral fracture, causing a collapse in the vertebral body and intervertebral disk height, aggravating segmental kyphosis, and consequently resulting in spinal segmental instability [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%